2010
DOI: 10.1038/nature08758
|View full text |Cite
|
Sign up to set email alerts
|

Neural bases for addictive properties of benzodiazepines

Abstract: Benzodiazepines are widely used in clinics and for recreational purposes, but will lead to addiction in vulnerable individuals. Addictive drugs increase the levels of dopamine and also trigger long-lasting synaptic adaptations in the mesolimbic reward system that ultimately may induce the pathological behavior. The neural basis for the addictive nature of benzodiazepines however remains elusive. Here we show that benzodiazepines increase firing of dopamine neurons of the ventral tegmental area through the posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
334
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 321 publications
(368 citation statements)
references
References 45 publications
29
334
1
4
Order By: Relevance
“…Supporting this, the a1-sparing compound, TPA023, was not self-administered by baboons up to doses that completely occupied benzodiazepine binding sites as measured via positron emission tomography (Ator et al, 2010). Moreover, mice with point mutations rendering the a1GABA A receptor insensitive to benzodiazepines did not show a preference for oral midazolam vs sucrose solutions, in contrast to wild-type mice (Tan et al, 2010). We have shown, however, that the a1-sparing compound, L-838,417, was reliably self-administered by rhesus monkeys (Rowlett et al, 2005), a finding clearly inconsistent with the hypothesis that a1GABA A receptors mediate the reinforcing effects of benzodiazepines.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Supporting this, the a1-sparing compound, TPA023, was not self-administered by baboons up to doses that completely occupied benzodiazepine binding sites as measured via positron emission tomography (Ator et al, 2010). Moreover, mice with point mutations rendering the a1GABA A receptor insensitive to benzodiazepines did not show a preference for oral midazolam vs sucrose solutions, in contrast to wild-type mice (Tan et al, 2010). We have shown, however, that the a1-sparing compound, L-838,417, was reliably self-administered by rhesus monkeys (Rowlett et al, 2005), a finding clearly inconsistent with the hypothesis that a1GABA A receptors mediate the reinforcing effects of benzodiazepines.…”
Section: Introductionmentioning
confidence: 76%
“…Benzodiazepines decrease firing of these interneurons via a1GABA A receptors, resulting in a net effect of decreased activity, ie, 'disinhibition', of DA neurons. The ultimate outcome would be an increase in DA release in the nucleus accumbens (NAc; Tan et al, 2010;2011), although this effect has yet to be established for benzodiazepines (eg Finlay et al, 1992;Murai et al, 1994). If this hypothesis is correct, then compounds lacking activity at a1GABA A receptors (ie, 'a1-sparing compounds') should lack abuse potential (Tan et al, 2010;2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, they represent an imperative initial step that triggers synaptic changes in addiction if the use of drug becomes chronic. Furthermore, it has been shown that benzodiazepine-induced changes in synaptic plasticity depend on α1-containing GABA A receptors because the observed changes are abolished in α1-H101R knock-in mice [19] . In our model, a single dose of zolpidem and short-term intermittent zolpidem treatment did not induce molecular changes at GABA A receptors regarding receptor number and GABA potentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided evidence that benzodiazepines share the pharmacological profile of addictive drugs through cell-type specific expression of α1-containing GABA A receptors [13,14,19] . Non-benzodiazepine zolpidem acts selectively at α1 subunit-containing GABA A receptors and is considered to be devoid of addiction liability.…”
Section: Discussionmentioning
confidence: 99%